Rig Services and Taxation - Petter Osmundsen (Center for Economic Studies and ifo Institute (CESifo), 2014)
A long period of rig scarcity and high rates has led to innovation in the procurement of rig services and in relationships between oil companies and rig contractors. Discussions have been conducted on joint ventures between companies and contractors, for instance. This paper describes and analyses such a solution from a taxation perspective. Could a joint venture pose problems for revenue capture from the petroleum sector? Challenges in taxing drilling services - including recently adopted British restrictions on determining internal charter rates for drilling units - are also analysed. In addition to analysing topical issues related to taxation and rigs, the paper makes a general contribution by highlighting the connection between taxing rig services at oil-company and rig-contractor levels, and by placing rig taxation in a broader resource management perspective.
Keywords: L60; K40; M11; H25; H27; 330; rig services; transfer pricing; tax planning